Hubungan Penggunaan Gadget Dengan Picky Eater Anak Kelas 3 dan 4 di SD Islam Mufidah Surabaya - Nurhayati, Ceria; Imroatul Farida; Alifiya Putri Shofiyanti (2025)
Parenting patterns and gadget use play an important role in shaping eating habits in children, both of which can cause picky eaters. This study aims to analyze the relationship between gadget use and picky eater incidents at school age. This study is an Analytical study included in the Cross Sectional Study, data analysis in this study using the Spearman Rho Test. because both variables use an ordinal data scale. The data collection tool used in this preliminary study was a questionnaire. The results of the study showed that sufficient gadget use or with a duration of 2-3 hours / day will cause children to become picky eaters, namely 38 students (52.1%), the category of good gadget use level was 23 students (31.5%) and the level of bad gadget use was 12 students (16.4%). There is a significant relationship between gadget use and picky eater incidents at school age. Suggestions for further research are expected to increase the contribution of knowledge, especially to parents about overcoming gadget use, one of which is by increasing the level of knowledge about gadget use.